The Matter of the Spirit: Ontology or Semiotics? - Galofaro , Francesco (E|C, 2023)
In the first part of the paper the notion of matter will be considered as purport or mening (meaning) without metaphysical connotations. It will be also meant as inherence, i.e., the orientation of the subject towards a value. Starting from a semiotic work on the purport, in fact, some characteristics become the form of value in view of a subject. The second part will show how different texts, from Paul to Edith Stein through Plutarch, John Damascene, Thomas Aquinas, Teresa of Avila, Leibniz, Florensky and Wittgenstein, construct the metaphysical opposition between matter and spirit by attributing different values to the two terms. Thus, purport precedes matter in the ontological acceptation. The third part summarizes the first two: there is no pre-semiotic or extra-semiotic matter; the discourse about ontology can think of matter only within a semiotics of value. In this frame, the principle of inherence will be considered as an operator who organizes purport (meaning) into a value and a subject for whom such a value is worth through semiotic work.